dinamika pemikiran Islam Indonesia dalam perspektif epistemologi fiqh dan kontribusinya bagi peneguhan semangat kebangsaan dan keindonesiaan - Ghufron, Fathorrahman (STAIN Kediri, 2016)
This paper will examine the epistemology of Islamic jurisprudence from the perspective of which the dynamics of Islamic thought since the beginning of independence era until the reform era is understood. Through the three aspects of epistemology, i.e. Bayānī, Ta’līlī, and Istiṣlāḥi, the author tries to analyze the different ways of view and the characteristics of thoughts between each group in expressing their Islamic thinking. It found out that the diversity of thoughts which go along with the dynamics of Islamic thinking has also an impact on the construction of strengthening nationality and Indonesia-ness. Keywords: Dynamics of Thought, Epistemology of Fiqh, Indonesia-ness Surat Keterangan Penulis